Preliminary research of biological plasticity of the third-year-old population of Chinese mitten crab (Eriocheir sinensis) - PENG Fei; FANG Di’an; ZHOU Yanfeng; TANG Yongkai; XU Dongpo; LIU Kai; SU Shengyan; YOU Yang (浙江大学学报. 农业与生命科学版)
There are sporadic immature individuals in the natural migration population of Chinese mitten crab (Eriocheir sinensis). The low temperature environment with high latitude and high altitude can significantly increase the proportion of immature individuals and facilitate collection. In this study, experiments were carried out to verify whether it can grow or reproduce normally in the subsequent third-year-old stage. In the spring of 2018, the two-year-old immature individuals from the Koluke Lake in Qinghai Province were collected as crab larvae and moved back to the ponds in the Yangtze River Basin for breeding, and the third-year-old crab was obtained for the first time. The experimental results showed that: 1) After domestication, the Chinese mitten crab population could successfully molt and grow in the ponds; the growth performance was similar to that of the conventional cultured crab, and the cultivated size was larger than that of the adult crab in the Koluke Lake area. 2) The third-year-old male and female individuals could be sexually mature, and the fecundity was similar to that of conventional crabs, and their offspring could be obtained by raising seedlings in earth ponds. 3) The nutritional compositions of third-year-old crabs cultured in ponds were intact, and some indexes were significantly different from those of conventional crabs, which might be related to the life history of plateaus and lakes. The results also showed that the size of the two-year-old immature crab was smaller than that of the conventional crab of the same age, and the size of the pond-cultured crab in the third-year-old stage was significantly larger than that of the Koluke Lake crab in the same period, indicating the existence of low temperature diapause and compensatory growth in the life history of E. sinensis. To sum up, the life cycle of the third-year-old crab population is more complex, and its nutrient deposition characteristics, mineral element contents, phased growth and accumulated temperature differences can provide new references for exploring the mechanism of low temperature diapause, life cycle prolongation and compensatory growth of the invertebrates.